If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 3 = t + -18 Reorder the terms: 3 + 4t = t + -18 Reorder the terms: 3 + 4t = -18 + t Solving 3 + 4t = -18 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 3 + 4t + -1t = -18 + t + -1t Combine like terms: 4t + -1t = 3t 3 + 3t = -18 + t + -1t Combine like terms: t + -1t = 0 3 + 3t = -18 + 0 3 + 3t = -18 Add '-3' to each side of the equation. 3 + -3 + 3t = -18 + -3 Combine like terms: 3 + -3 = 0 0 + 3t = -18 + -3 3t = -18 + -3 Combine like terms: -18 + -3 = -21 3t = -21 Divide each side by '3'. t = -7 Simplifying t = -7
| 8+2x*3=x*4+12 | | a^2x+3x=2a^2 | | x^2-5.75+7.75=6 | | x^2-5.75+7.75=1 | | x^2-5.75+7.75=4 | | x^2-5.75+7.75=2 | | 2x^2-4x+8.8=2 | | 2x^2-4x+18.2=2 | | 5a^2-6a=1 | | (10b-6)-3(3b+2)=-3 | | x^2-8x+15.75=0 | | y=0(0)-7 | | (4y+9)(4y+9)=64y^3+432y^2+972y+729 | | 5c+6=2-y | | 5x+6x+3+8=3x+5+7x | | 16+-8-9= | | z^2-8z-20= | | 3(Q-6)=2(2Q+7)+10 | | 25+-15-12= | | 15x^2+5x-20= | | y=18(0)+0 | | 9y^2+21y+6= | | 2x+3x=30-z | | y=-7(0)+4 | | 3x^2-4y=20 | | 3x^2-4y=20 | | 5(t-3)+7t=4(3t+3)-10 | | 2x^2+5y^2=30 | | -2(5s-6)-12=-2(7s+2)-3 | | 0.25(x-2)=8 | | 5(y+1)+3=3y-20 | | 10+b+10=35 |